MENUMBUHKAN BUDAYA INVESTASI MELALUI EDUKASI DAN LITERASI KEUANGAN PADA KELOMPOK IBU RUMAH TANGGA DI SAWANGAN DEPOK - Fatimah, Fatimah; Endang Purwaningrum; Lini Ingriyani; Indianik Aminah; Zulmaita (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Education and financial literacy are very important to increase community understanding in managing finances, including housewives. Lack of financial literacy can make people tend to invest in real form, such as buying a house or land, which is difficult to resold. In an effort to increase financial literacy, the Jakarta State Polytechnic Financial Management Study Program held training in Sawangan, Depok, for 40 members of the Dharma Wanita Unity BSSN. The training was carried out in a luring with two main activities: lectures and discussions about financial literacy, as well as investment simulation assistance using stockbit applications. The activity began with a pre-test and ended with a post-test, showing an increase in participants' knowledge, with an average score of the final test rising from 83.21 to 95.32. The statistical test using SPSS shows significant changes (p <0.05). For two weeks of assistance, 12% of participants managed to invest in stocks. The activity was closed with the formation of the WhatsApp group to continue to assist participants in capital market investment. In the future, the Community Service Team plans to expand the reach of activities to other cities around Depok, so that more people can feel the benefits.